Espaços livres públicos de Belo Horizonte como campo de construção de conhecimento em arte - Clara Mendes de Oliveira Cesar (2020)
This work investigates different approached to Art teaching through identifying and analysing the activities of teacher/artists for whom the city is an element of teaching practice and artistic creation. Observations were made in field studies of three artistic activities that were undertaken in the streets and squares of Belo Horizonte by the teacher/artists who took part in the research. The teaching practices, together with interviews conducted with the teacher/artists, were recorded by digital audio-visual means and analysed in the light of theoretical reference points and works of art related to the theme. At the same time, consideration was given to the different approaches of the teacher/artists to urban public spaces as an element in constructing their art teaching/production. Comments have been made throughout the work in relation both to the construction of Art knowledge in urban spaces, and to both formal and informal education. The work aims to interrelate poetry and teaching in the training and practice of teacher/artists.